2019
DOI: 10.1016/j.powtec.2018.10.034
|View full text |Cite
|
Sign up to set email alerts
|

DEM analysis of the effect of particle shape, cohesion and strain rate on powder rheometry

Abstract: Discrete Element Method (DEM) is used to simulate the flow of particles addressing the influence of shear strain rate, particle shape and cohesion on the flow characteristics. For this purpose, the dynamics of particle motion in the Freeman Technology FT4 rheometer is analysed. The simulations are first validated by comparison with experiments with cohesive particles, i.e. silanised glass beads, from the literature. Particles with faceted shapes, sharp corners and edges are then simulated and found to require … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 40 publications
(55 reference statements)
0
29
0
Order By: Relevance
“…They measured the work (basic flow energy) required to penetrate the rotating impeller into the cohesive powder bed, and showed that this could also be quantitatively predicted by DEM using the elasto-plastic adhesive model of Pasha et al (2014). Bulk cohesion simply lifts up the baseline of powder resistance to bulk motion and the functional dependence on the shear strain rate has the same trend, as recently analysed by Vivacqua et al (2019). They simulated the FT4 test using DEM for both cohesive (two levels) and cohesionless contacts, using Luding's contact model (Luding, 2008) and calculated the shear stress on the impeller blade as a function of the impeller tip speed, as shown in Fig.…”
Section: Effect Of Cohesionmentioning
confidence: 67%
See 4 more Smart Citations
“…They measured the work (basic flow energy) required to penetrate the rotating impeller into the cohesive powder bed, and showed that this could also be quantitatively predicted by DEM using the elasto-plastic adhesive model of Pasha et al (2014). Bulk cohesion simply lifts up the baseline of powder resistance to bulk motion and the functional dependence on the shear strain rate has the same trend, as recently analysed by Vivacqua et al (2019). They simulated the FT4 test using DEM for both cohesive (two levels) and cohesionless contacts, using Luding's contact model (Luding, 2008) and calculated the shear stress on the impeller blade as a function of the impeller tip speed, as shown in Fig.…”
Section: Effect Of Cohesionmentioning
confidence: 67%
“…Nevertheless, to use FT4 and Anton Paar instruments as powder rheometers, it is clearly necessary to analyse the mechanics of powder flow induced by the impeller and relate the expended work to the bulk powder rheological characteristics. For this purpose, Ghadiri and co-workers have carried out a systematic study of the effects of cohesion, air drag and strain rate, and particle shape on bulk powder rheology by analysing the stress and strain fields within FT4 using numerical simulations by a combined DEM-CFD approach (Nan et al, 2017a, b, c;Vivacqua et al, 2019). With current computer power and memory, it is too challenging to use fine cohesive powders with a complex shape in such simulations.…”
Section: Ft4 Powder Rheometer Of Freeman Technologymentioning
confidence: 99%
See 3 more Smart Citations